Semiotic Analysis of the Meaning of Social Support in the Lyrics of the Song Pelukku Untuk Pelikmu by Fiersa Besari - Hidayat, Rachmat; Nurliah, Nurliah (Journal International of Lingua and Technology, 2023)
"Pelukku Untuk Pelikmu" is a musical work from a musician and book writer, Fiersa Besari. It was released as the soundtrack of the movie "Imperfect: Career, Love, & Scales" in 2019. Carrying the theme of self-confidence from one's insecure nature, this song is also intended for those who experience downturns and experience mental decline due to various problems in life so that they need positive encouragement to rise from these conditions. Therefore, indicators of social support are closely related and can be measured using sign analysis proposed by Ferdinand de Saussure. In his theory, Saussure describes five language concepts in the linguistic system that can be a knife to dissect the meaning of a text or sentence. Meanwhile, social support is divided into four types, namely emotional support, information support, instrumental/real support, and friendship support. The results of the meaning in the song lyrics will then classify each sentence in it into one of these types of support. The approach used in this research is descriptive qualitative by analyzing the relationship between Ferdinand de Saussure's semiotic theory and the concept of social support and then drawing conclusions based on the results of the analysis.